Effectiveness of the use of an oscillating positive expiratory pressure device in bronchiectasis with frequent exacerbations: a single-arm pilot study - Kim, So Rae; Kim, Sun-Hyung; Kim, Geun-Hyeong; Cho, Jun Yeun; Choi, Hayoung; Lee, Hyun; Ra, Seung Won; Lee, Ki Man; Choe, Kang Hyeon; Oh, Yeon-Mok; Shin, Yoon Mi; Yang, Bumhee (Frontiers in Medicine, 2023)
Impaired airway clearance in patients with non-cystic fibrosis bronchiectasis causes frequent bacterial infection, chronic inflammation, and progressive tissue destruction. We aimed to evaluate whether an oscillating positive expiratory pressure (OPEP) device could allow effective sputum expectoration and prevention of acute exacerbations in patients with bronchiectasis who had frequent acute exacerbations. This open-label, single-arm, prospective study was conducted on 17 patients who experienced three or more acute exacerbations in the past year. We evaluated the prevention of acute exacerbations, subjective symptom improvement, and sputum amount change during the use of the Aerobika (TMI, London, ON) OPEP device twice daily for 6 months. Of all enrolled patients, only two acute exacerbations occurred during the study period, indicating a significant decrease compared with the number of acute exacerbations before the device use (p <0.001). Additionally, Bronchiectasis Health Questionnaire score changed from 58.7 to 66.6, showing significant improvement over the treatment period (p < 0.001). The largest sputum volume was observed 3 months after OPEP device use (baseline: 10ml, 3rd month 25ml, p=0.325). There were no major adverse events related to the use of OPEP devices. Twice-daily physiotherapy with OPEP device in patients with bronchiectasis who have frequent exacerbations may facilitate symptomatic improvement and prevention of acute exacerbations without serious adverse events.